Plato as critical theorist - Thakkar, Jonny, 1982- (Harvard University Press, 2018)
Is there any point in thinking about the best possible society? Over the last decade or so, a number of political philosophers have argued that such "ideal theory" is a dangerous distraction from the concrete power struggles that make up "real politics." Jonny Thakkar takes a different view, arguing that each and every one of us has a duty to engage in ideal theory. To make that case he turns to Plato's Republic, which depicts an ideal society within which ideal theory itself plays a vital role, thanks to the institution of philosopher-kings. The first half of the book offers a careful but creative reading of the notion of rule by philosophers. The second half of the book argues that in today's liberal democracies what we need is not philosopher-kings but philosopher-citizens--citizens who reflect, both individually and together, on how they could work together to produce an environment conducive to flourishing. Plato as Critical Theorist argues that the notion of philosopher-citizens is not only compatible with Rawlsian political liberalism, but an advance on it.--